A Numerical Approach to Analyze the Performance of a PEF-Ohmic Heating System in Microbial Inactivation of Solid Food - Moya, J.; Astráin-Redín, L.; Grasa, J.; Cebrián, G.; Calvo, B.; Álvarez, I. (Frontiers in Food Science and Technology, 2022)
Pulsed Electric Fields (PEF) technology has been recently proposed as a new ohmic-heating system for the heat treatment of solid products in short periods (less than 1 min). However, similar to traditional ohmic heating, non-homogeneous distribution of temperature has been observed and cold points appeared in the interphase between the solid treated product and the electrodes, which can limit the technology for assuring food safety for treated solid products. In this investigation, a computational axisymmetric model of a lab-scale PEF system for a solid product (agar cylinder) was developed. This model was used to predict the temperature and the electric field distribution, treatment time, and the microbial inactivation (Salmonella Typhimurium 878) in the solid product after a PEF-ohmic treatment. Using a factorial analysis, a total of 8 process conditions with different settings of applied field strength levels (2.5–3.75 kV/cm), frequencies (100–200 Hz), and initial agar and electrode temperature (40–50°C) were simulated for the agar cylinder in order to identify the effect and optimal values of these parameters, which offer the most temperature homogeneity. The results showed that the initial temperature of the agar and the electrodes was of great importance in achieving the best temperature uniformity, limiting the occurrence of cold points, and therefore, improving the homogeneity in the level of inactivation of Salmonella Typhimurium 878 all over the agar cylinder. A treatment of 2.3 s would be enough at 3.75 kV/cm, 200 Hz with an initial temperature of 50°C of the agar and the electrodes, for a 5-Log10 reduction of Salmonella Typhimurium 878 in the whole product with a deviation of 9°C between the coldest and hottest point of the solid.